Use of comprehensive chromosomal screening for embryo assessment: microarrays and CGH. - Wells, D; Alfarawati, S; Fragouli, E (Oxford University Press, 2008)
One of the most important factors influencing embryo viability is chromosome imbalance (aneuploidy). Embryos derived from aneuploid gametes have little potential for forming a viable pregnancy, but cannot be distinguished from normal embryos using standard morphological evaluation. For more than a decade, preimplantation genetic screening (PGS) has been used to assist in the identification of aneuploid embryos. However, current strategies, based upon cell biopsy followed by fluorescent in situhybridization, allow less than half of the chromosomes to be screened. In this review, we discuss methods that overcome the limitations of earlier PGS strategies and provide screening of the entire chromosome complement in oocytes and embryos. In recent months, there has been a rapid growth in the number of PGS cycles utilizing one such method, comparative genomic hybridization (CGH). Data from IVF cycles utilizing CGH must be considered preliminary, but appear to indicate a dramatic increase in embryo implantation following comprehensive chromosomal screening. It is expected that methods based upon microarrays will yield similar clinical results and may be sufficiently rapid to permit comprehensive screening without the need for embryo cryopreservation. Some microarray platforms also offer the advantage of embryo fingerprinting and the potential for combined aneuploidy and single gene disorder diagnosis. However, more data concerning accuracy and further reductions in the price of tests will be necessary before microarrays can be widely applied.